Silicato de cálcio e magnésio e calcário dolomítico na sanidade de grandes culturas e incremento do teor de silício e disponibilidade de Fósforo em Latossolo Vermelho Distroférrico - Sord, Cindia (2024)
Soybean (Glycine max), corn (Zea mays), and wheat (Triticum aestivum) crops are the basis of national agricultural chains. Thus, alternatives that increase the productivity of these crops are relevant. Silicon is a beneficial element for plant nutrition, and can prompt health and resistance to crops against biotic and abiotic stresses. The objective of this work was to evaluate the contribution of calcium and magnesium silicate and dolomitic limestone to the productivity of these crops, as well as the effects on the chemical and physical properties of the soil. The experiment was carried out in a commercial agricultural area in the municipality of Céu Azul-PR, in the 2020-2021, 2022-2023 harvests and second harvest of corn in the year 2023. The experimental design used was completely randomized with 3 treatments and 10 replications, totaling 30 experimental units, arranged in strips, as the experiment was mechanized and in a commercial area. Doses of 0, 300, and 800 kg ha-1 were defined for the treatments, control, calcium and magnesium silicate, and dolomitic limestone, respectively. At each point, physical soil samples were collected to determine particle and apparent density, macroporosity, microporosity, and total porosity, as well as soil samples to determine chemical parameters, organic matter (OM), phosphorus (P), pH in CaCl2, SMP, H + Al, potassium (k), calcium (Ca), magnesium (Mg), base sum (SB) and base saturation (V%). Resistance to soil penetration was evaluated with an impact penetrometer. The chlorophyll and carotenoid contents were quantified for the soybean cultivar and the corn hybrid. Primary leaf macronutrients and productivity of wheat and corn crops were evaluated. The data were submitted to ANOVA, and when there was a difference at 5% significance, Tukey's mean comparison test was performed at 5%. It was concluded that the treatments did not provide improvements in apparent density, macroporosity, microporosity, and total porosity. The degree of compaction was greater in the silicate treatment. The variables carotenoids, chlorophyll 'a', chlorophyll 'b' and total chlorophyll showed no differences between treatments in the years 2020/2021 in the soybean crop and corn crop, harvest 2023. In the soybean crop, in the 2022/2023 harvest, the limestone treatment presented a lower value for chlorophyll 'b', while carotenoids, chlorophyll 'a' and total chlorophyll presented a lower value for silicate. The chemical properties of soil phosphorus (P), pH in CaCl2 and SMP presented higher values for the year 2022. However, evaluating chemical properties for the three treatments, SMP presented the highest value for the control. For leaf macronutrients, potassium in corn presented the highest value in the silicate treatment. The productivity values for wheat and corn crops did not show a significant result, and no increase was revealed for the silicate and limestone treatments.